2011
DOI: 10.1089/scd.2010.0125
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 17-β Estradiol on Enhancing Proliferation of Human Bone Marrow Mesenchymal Stromal Cells In Vitro

Abstract: Human bone marrow mesenchymal stromal cells (MSCs) with self-renewal and multiple differentiation potentials are considered a possible cell source for tissue engineering and regenerative medicine. However, the limited amount of MSCs in bone marrow and the loss of differentiation capacity following in vitro expansion restrict their practical application. Effective improvement of MSC proliferation is necessary for the clinical application of MSC-based tissue engineering. The effects of estrogen supplements on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 41 publications
3
48
0
1
Order By: Relevance
“…Although an ideal cell type for transplantation due to availability of convenient methods and their presence in large cell quantities, ASCs still remain elusive with respect to effects mediated by estrogen receptor α and β. Like other MSCs, ASCs express the typical mesenchymal markers CD29 and CD90 [34]. In the present study, we demonstrated that activation of ERα and β results in no changes of the phenotypic features of ASCs.…”
Section: Discussionsupporting
confidence: 57%
“…Although an ideal cell type for transplantation due to availability of convenient methods and their presence in large cell quantities, ASCs still remain elusive with respect to effects mediated by estrogen receptor α and β. Like other MSCs, ASCs express the typical mesenchymal markers CD29 and CD90 [34]. In the present study, we demonstrated that activation of ERα and β results in no changes of the phenotypic features of ASCs.…”
Section: Discussionsupporting
confidence: 57%
“…19 For adipogenesis, the medium is supplemented with 500nM dexamethasone, 10mM insulin, and 0.5mM isobutyl-methylxanthine. 30 Real-time PCR was used to quantify the gene expression of specific markers of MSC differentiations because it is a well-established technique to quantify the gene messenger RNA (mRNA) expressions of differentiation markers to reflect differentiation levels of MSC. The levels of mRNA are generally correlated to protein expression and are more sensitive than protein measurements for short-term observations.…”
Section: Proliferation Capability Of Human Msc Cultured With Gr Sirnamentioning
confidence: 99%
“…Reduced stromal/osteoprogenitor population in the BM of Ovx animals has been reported. Available studies also indicate that E2 deficiency diminishes MSC renewability and osteogenic differentiation of BM-MSC which could lead to poor bone regeneration upon systemic transplantation [23,24].…”
Section: Introductionmentioning
confidence: 99%